Soil temperature and soil moisture dynamics in winter and spring under heavy snowfall conditions in North‐Eastern Japan. Issue 15 (1st June 2020) - Brandt, Alexander C.; Zhang, Qiqin; Lopez Caceres, Maximo Larry; Murayama, Hideki
Abstract: Warm winters and high precipitation in north‐eastern Japan generate snow covers of more than three meters depth and densities of up to 0.55 g cm −3 . Under these conditions, rain/snow ratio and snowmelt have increased significantly in the last decade under increasing warm winters. This study aims at understanding the effect of rain‐on‐snow and snowmelt on soil moisture under thick snow covers in mid‐winter, taking into account that snowmelt in spring is an important source of water for forests and agriculture. The study combines three components of the Hydrosphere (precipitation, snow cover and soil moisture) in order to trace water mobility in winter, since soil temperatures remained positive in winter at nearly 0.3°C. The results showed that soil moisture increased after snowmelt and especially after rain‐on‐snow events in mid‐winter 2018/2019. Rain‐on‐snow events were firstly buffered by fresh snow, increasing the snow water equivalent (SWE), followed by water soil infiltration once the water storage capacity of the snowpack was reached. The largest increase of soil moisture was 2.35 vol%. Early snowmelt increased soil moisture with rates between 0.02 and 0.035 vol% hr −1 while, rain‐on‐snow events infiltrated snow and soil faster than snowmelt and resulted in rates of up to 1.06 vol% hr −1 . These results showed the strong connection of rain, snow and soil in winter and introduce possible hydrological scenarios in the forest ecosystems of the heavy snowfall regions of north‐eastern Japan. Effects of rain‐on‐snow events and snowmelt on soil moisture were estimated for the period 2012–2018. Rain/snow ratio showed that only 30% of the total precipitation in the winter season 2011/2012 was rain events while it was 50% for the winter 2018/2019. Increasing climate warming and weakening of the Siberian winter monsoons will probably increase rain/snow ratio and the number of rain‐on‐snow events in the near future. Abstract : Soils in Japanese heavy snow fall areas do not freeze in winter. Rain‐on‐snow events caused soil moisture increase rates of (0.3–1 vol% hr −1 ) as well as an increase in snow water equivalent (SWE); snowmelt events cause a slower increase of soil moisture (<0.2 vol% hr −1 ) and a decrease in SWE. The rain/snow ratio in winter increased from 0.47 in 2012 to almost 1 in 2019.